Blue Monday. 2, Absolute beginners - Clugston-Flores, Chynna (2016)
"Teenage warfare between the hormone-crazed girls and boys of Jefferson High erupts! The gang throws a fancy dinner party, but after the boys attempt to videotape Bleu taking a bath, the whole ordeal ends in a social status disaster. To restore her ruined reputation, Bleu agrees to go on a date with Alan in exchange for the evidence"--Back cover.
Contains material originally published in single magazine form as Blue Monday: Absolute beginners #1-4.
Rated T / Teen.
Keywords: Ant, Adam -- Comic books, strips, etc; Teenagers -- Comic books, strips, etc; Rock concerts -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Romance comics; Graphic novels; Comics (Graphic works)